Can P-glycoprotein mediate resistance to nilotinib in human leukaemia cells? - Kosztyu, Petr; Dolezel, Petr; Mlejnek, Petr (Pharmacological research, 2013)
The effect of P-glycoprotein (P-gp, ABCB1, MDR1) expression on cell resistance to nilotinib was studied in human leukaemia cells. We used K562/Dox cells overexpressing P-gp and their variants (subclones) with a gradually decreased P-gp expression. These subclones were established by stable transfection of K562/Dox cells with a plasmid vector expressing shRNA targeting the ABCB1 gene. Functional analysis of P-gp using a specific fluorescent probe indicated gradually decreased dye efflux which was proportional to the P-gp expression. We observed that K562/Dox cells overexpressing P-gp contained a significantly reduced intracellular level of nilotinib when compared to their counter partner K562 cells, which do not express P-gp. This effect was accompanied by a decreased sensitivity of the K562/Dox cells to nilotinib. Importantly, cells with downregulated expression of P-gp gradually lost their ability to decrease the intracellular level of nilotinib although they still significantly decreased the intracellular level of daunorubicin (DNR). Accordingly, cells with the reduced expression of P-gp concomitantly failed to provide resistance to nilotinib, however, they exhibited a significant resistance to DNR. Taken together, we demonstrated that the conclusion as to whether P-gp is involved in nilotinib resistance or not strongly depends on its expression at protein level.
Keywords: viabilita buněk; leukemie; protinádorové látky; Cell Proliferation; chemorezistence; Pyrimidines; Cell Survival; inhibitory proteinkinas; ATP Binding Cassette Transporter, Subfamily B, Member 1; buňky K562; Leukemia; lidé; P-glykoprotein; Humans; pyrimidiny; Protein Kinase Inhibitors; K562 Cells; proliferace buněk; Drug Resistance, Neoplasm; Antineoplastic Agents